The Relationship between Nutritional Status and Menstrual Blood Volume among Adolescent Girls at A Boarding School - Qonita Luthfiah; Eva Rianti Indrasari; Yafma Femin Helta Heriady; Mirasari Putri (Global Medical & Health Communication (GMHC), 2026)
Menstruation is an essential physiological process in adolescent girls. Reflecting not only reproductive health but also overall health status. Menstrual disorders, particularly heavy menstrual bleeding (menorrhagia), are common among adolescents, with a prevalence of approximately 12–37%. Nutritional status plays a key role in menstrual health. In adolescents with overnutrition, excess body fat can increase estrogen production, which may subsequently affect the menstrual cycle, including the volume of menstrual blood. In boarding school settings, where students live under structured schedules and share dietary patterns, nutritional imbalances are common and may disrupt menstrual patterns. This study aimed to determine the relationship between nutritional status and menstrual blood volume among adolescent girls at a boarding school in Bogor, West Java,  Indonesia, in 2025. It was an observational analytic study with a cross-sectional design involving 85 adolescent girls aged 15–17 years, selected through stratified random sampling according to predefined inclusion and exclusion criteria. Primary data were obtained from menstrual pictogram forms and measurements of body mass index (BMI) and waist circumference. Data were analyzed using univariate and bivariate analyses with the chi-square test. Among the 85 participants, 35 experienced menorrhagia, including all 15 who were classified as overnutrition based on BMI, and 11 participants with increased waist circumference. Fisher’s Exact tests for both BMI and waist circumference against menstrual blood volume yielded p-values <0.001 (p<0.005), indicating a highly significant association. In conclusion, higher BMI and greater waist circumference were strongly associated with increased menstrual blood volume among adolescent girls at a boarding school in Bogor. Nutritional balance and weight control are essential to support healthy menstrual patterns in this population.